2003
DOI: 10.1159/000072008
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Necrosis Factor-α in Comparison to Adenosine Deaminase in Tuberculous Pleuritis

Abstract: Background: Adenosine deaminase (ADA) is already used for the differential diagnosis of tuberculosis pleurisy. Tumour necrosis factor-α (TNF) is another marker which has been investigated for this purpose. Objective: We evaluated the diagnostic value of pleural fluid and serum TNF concentrations in tuberculous pleuritis and compared them to ADA. Methods: Sixty-two patients (24 tuberculous pleuritis, 38 non-tuberculous pleuritis) with exudative pleurisy were included. Serum and pleural fluid TNF concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 12 publications
2
22
2
1
Order By: Relevance
“…Vankayalapati et al [26] reported that IL-18 and IFN gamma concentrations are higher in the pleural fluid of TB patients than in patients with other diseases. In another study, pleural fluid TNF alpha levels and pleural fluid/serum TNF alpha were higher in tuberculous effusions than in other exudates, but their diagnostic value appears to be poorer than that of ADA [27]. Our result differs from these studies [26,27] and we did not find a clear explanation.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Vankayalapati et al [26] reported that IL-18 and IFN gamma concentrations are higher in the pleural fluid of TB patients than in patients with other diseases. In another study, pleural fluid TNF alpha levels and pleural fluid/serum TNF alpha were higher in tuberculous effusions than in other exudates, but their diagnostic value appears to be poorer than that of ADA [27]. Our result differs from these studies [26,27] and we did not find a clear explanation.…”
Section: Discussioncontrasting
confidence: 93%
“…In another study, pleural fluid TNF alpha levels and pleural fluid/serum TNF alpha were higher in tuberculous effusions than in other exudates, but their diagnostic value appears to be poorer than that of ADA [27]. Our result differs from these studies [26,27] and we did not find a clear explanation. We speculate that there was a barrier separating the pleural fluid and the host's immune response due to pleural fibrosis present in patient 16.…”
Section: Discussioncontrasting
confidence: 93%
“…In the past, several biological markers have been studied to aid the diagnosis of plTB, including the measurement of pleural fluid concentrations of adenosine deaminase [50,51], tumour necrosis factor-a [52][53][54] and whole IFN-c [50,55,56], with reported diagnostic sensitivities ranging from 72-88% and specificities from 88-100% [50][51][52][53][54][55][56]. Thus, reported sensitivities of adenosine deaminase and IFN-c measurements in PE for the diagnosis of plTB are similar to the sensitivity of the T-SPOT.TB test reported in the present study, although T-SPOT.TB specificity seems lower.…”
Section: Discussionmentioning
confidence: 99%
“…En relación a la prueba de ADA como diagnóstica de tuberculosis pleural, diversos autores han encontrado diferentes puntos de corte, que varían desde 30 hasta 100 UI/L (tabla 2) (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) , dependiendo esto del grupo de pacientes que formaron parte del estudio, la población cuya epidemiología del Mycobacterium es distinta y los criterios tomados en cuenta para el diagnóstico definitivo de las diferentes enfermedades que ocasionaron el derraTabla 2. Estudios realizados a lo largo del tiempo sobre el valor de la prueba de ADA y sus principales parámetros.…”
Section: Discussionunclassified